Approximate Fixed Point Theorems in Fuzzy Norm Spaces for an Operator - S. A. M. Mohsenalhosseini; H. Mazaheri (Advances in Fuzzy Systems)
We define approximate fixed point and fuzzy diameter in fuzzy norm spaces. We prove theorems for various types of well-known generalized contractions on fuzzy norm spaces with the use of two general lemmas that are given regarding approximate fixed points of operators on fuzzy norm spaces.